Meningkatkan kemampuan pemahaman konsep matematis siswa melalui model pembelajaran kooperatif tipe think talk write (TTW) pada materi relasi dan fungsi kelas VIII SMP - Panggabean, Yosephin Elisabeth; Sibarani, Eva Margaretty (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2020)
The purpose of this classroom action research is to study whether the Think Talk Write (TTW) type of cooperative learning model can improve student’s mathematical concepts understanding abilities. The subjects in this study were 30 students of grade VIII-9 on Public Junior High School 4 Medan on the Academic Year of 2019/2020. The subject matters were about relations and functions. First, an initial test was given to find out the student’s mathematical understanding of mathematical concepts. The test results showed that the student’s ability to understand mathematical concept’s was low. It can be seen from 30 students, but only 8 or (26.67%) students passed the criteria. After testing the student’s ability on the first cycle, the percentage of students who passed the minimum criteria rose to 63.33% (19 students). And on the ability test of students in the second cycle, the percentage of students who passed the minimum criteria reached 86.67% (26 students). Based on the results, it was found that the Cooperative learning model of the Think Talk Write (TTW) type could improve the ability to understand mathematical concepts of grade VIII-9 students of Public Junior High School 4 Medan.